Positive mood and working memory in young preschool children. - Tang, Mavis Yi Wen. (2009)
The role of positive mood in working memory was studied in children at two ages (3 and 4 years) using the Self-Ordered Pointing Test (SOPT) in which children were required to point to a new picture stimulus in a set on each presentation without repeating the same picture. Half the children were induced with positive mood, and half was induced with neutral mood. Positive mood impaired children’s SOPT accuracy, particularly for the 4-year-olds. However, positive mood did not significantly affect children’s working memory span. These findings suggested that positive mood elicits an additional load on underlying executive processes (inhibition) in the service of working memory, decreasing cognitive resource capacity to devote to the task at hand.